Introduction to Central Banking - Bindseil, Ulrich; Fotia, Alessio (Springer Nature, 2021)
This open access book gives a concise introduction to the practical implementation of monetary policy by modern central banks. It describes the conventional instruments used in advanced economies and the unconventional instruments that have been widely adopted since the financial crisis of 2007–2008. Illuminating the role of central banks in ensuring financial stability and as last resort lenders, it also offers an overview of the international monetary framework. A flow-of-funds framework is used throughout to capture this essential dimension in a consistent and unifying manner, providing a unique and accessible resource on central banking and monetary policy, and its integration with financial stability. Addressed to professionals as well as bachelors and masters students of economics, this book is suitable for a course on economic policy. Useful prerequisites include at least a general idea of the economic institutions of an economy, and knowledge of macroeconomics and monetary economics, but readers need not be familiar with any specific macroeconomic models.